Penyusunan Enterprise Architecture Planning (EAP) Menggunakan TOGAF Pada PT. Pelabuhan Indonesia III (persero) - Prabowo, Ony; Amelia, Tan; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
PT. Pelabuhan Indonesia III (Persero) or PT. Pelindo III is a State-Owned Enterprise engaged in the sector transportation. Duties, powers and responsibilities of this company is to manage the public ports in seven provinces in Indonesia. PT. Pelindo III has a vision